Board gender diversity and firm performance: Unveiling the ESG effect - Muskan Sahu; Waleed M. Alahdal; Dharen Kumar Pandey; Saeed Rabea Baatwah; Mohammed Saleh Bajaher (Sustainable Futures)
This study uses a sample of 122 non-financial listed companies in Malaysia from 2016 to 2023 to examine the relationship between board gender diversity (BG) and firm performance (FP), with a focus on the moderating role of Environmental, Social, and Governance (ESG) performance. Using generalized least squares (GLS) estimation, the findings indicate that greater representation of women on corporate boards positively influences firm performance, leading to enhanced FP. Furthermore, ESG performance positively impacts return on equity (ROE) and Tobin's Q. Importantly, ESG performance moderates the relationship between BG and FP, particularly in the context of ROE. The study offers both theoretical and practical insights. It underscores the critical role of fostering transparency in ESG practices and enhancing gender diversity at the board level. These efforts drive better FP and contribute to long-term corporate sustainability.